Integrated transcriptome and metabolome analysis revealed that flavonoids enhanced the resistance of Oryza sativa against Meloidogyne graminicola - Zhang, Lianhu; Li, Songyan; Shan, Chonglei; Liu, Yankun; Zhang, Yifan; Ye, Lifang; Lin, Yachun; Xiong, Guihong; Ma, Jian; Adnan, Muhammad; Shi, Xugen; Sun, Xiaotang; et al. (Frontiers in Plant Science, 2023)
Rice is a crucial food crop worldwide, but its yield and quality are significantly affected by Meloidogyne graminicola, a root knot nematode. No rice variety is entirely immune to this nematode disease in agricultural production. Thus, the fundamental strategy to combat this disease is to utilize rice resistance genes. In this study, we conducted transcriptome and metabolome analyses on two rice varieties, ZH11 and IR64. The results indicated that ZH11 showed stronger resistance than IR64. Transcriptome analysis revealed that the change in gene expression in ZH11 was more substantial than that in IR64 after M. graminicola infection. Moreover, GO and KEGG enrichment analysis of the up-regulated genes in ZH11 showed that they were primarily associated with rice cell wall construction, carbohydrate metabolism, and secondary metabolism relating to disease resistance, which effectively enhanced the resistance of ZH11. However, in rice IR64, the number of genes enriched in disease resistance pathways was significantly lower than that in ZH11, which further explained the susceptibility of IR64. Metabolome analysis revealed that the metabolites detected in ZH11 were enriched in flavonoid metabolism and the pentose phosphate pathway, compared to IR64, after M. graminicola infection. The comprehensive analysis of transcriptome and metabolome data indicated that flavonoid metabolism played a crucial role in rice resistance to M. graminicola infection. The content of kaempferin, apigenin, and quercetin in ZH11 significantly increased after M. graminicola infection, and the expression of genes involved in the synthetic pathway of flavonoids also significantly increased in ZH11. Our study provides theoretical guidance for the precise analysis of rice resistance and disease resistance breeding in further research.